2016
DOI: 10.1080/15226514.2016.1207608
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cadmium on physiological parameters of cereal and millet plants—A comparative study

Abstract: Metal load is an abiotic stress that becomes stronger by continual industrial production, wastage, and long-range transport of contaminants. It deteriorates the conditions of agricultural soil that leads to lower growth of cereals as well as decreasing nutritional value of harvested grains. Cadmium (Cd) entry by food chain also affects the health of population. The present study is focused on finding out the superior cereal variety under increasing Cd regime. The plants were grown in increasing Cd levels (0-10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 42 publications
0
2
0
1
Order By: Relevance
“…Our results showed that chlorophyll a, chlorophyll b, total chlorophyll and total carotenoid content decreased under nickel toxicity. It has been well documented that decreases in chlorophyll content and photosynthetic efficiency are used to monitor the heavy metal-induced damage in leaves (Asopa et al 2016). Kamran et al (2016) have indicated that nickel toxicity leads to chlorophyll loss as a result of Mg and Fe deficiency in the leaves of plant species.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that chlorophyll a, chlorophyll b, total chlorophyll and total carotenoid content decreased under nickel toxicity. It has been well documented that decreases in chlorophyll content and photosynthetic efficiency are used to monitor the heavy metal-induced damage in leaves (Asopa et al 2016). Kamran et al (2016) have indicated that nickel toxicity leads to chlorophyll loss as a result of Mg and Fe deficiency in the leaves of plant species.…”
Section: Discussionmentioning
confidence: 99%
“…[ 30 ] Several researchers have reported the decrease in greenness index due to metal toxicity in plants. [ 42,43 ] Other researchers had reported reduction in greenness index and interruption of electron transport due to Ni toxicity in several studies. [ 35,44 ] At higher Ni, it was recorded that photosynthetic protein formed complexes leading to decrease in photosynthesis and greenness index.…”
Section: Resultsmentioning
confidence: 99%
“…It interferes with the activity of enzymes involved in chlorophyll synthesis, impairing the conversion of precursor molecules into functional chlorophyll molecules. As a result, chloroplasts within affected leaf cells become deficient in chlorophyll, leading to a noticeable loss of green colour [123,184]. Similarly, lead, another significant heavy metal pollutant, can inhibit various enzymes and metabolic pathways involved in chlorophyll biosynthesis.…”
Section: Chlorosismentioning
confidence: 99%